Tingkat Kapasitas Ketahanan Komunitas: (Kasus: Bagian Wilayah Perkotaan Malang Utara) - Chantika Putri, Jasmine; Surjono; Agus Setyono, Deni (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
In 2020 the National Disaster Management Agency stated that one of the cities that has low vulnerability to disasters is Malang City. Therefore, it is necessary to assess the resilience capacity of communities in the North Malang Urban Area who have vulnerability to social and environmental changes. This study uses the Resilient Capacity Index method to measure the resilience capacity of the community by considering ecological, physical, economic, human and social aspects. The results of the study in the form of an overview of aspects of community resilience in the northern Malang City area can be used as a support for the development of a more resilient city. Through measuring resilience capacity using standard score or z-score, it is known that the North Malang Urban Area has a moderate community resilience capacity level value.